2018
DOI: 10.1016/j.exer.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 14-3-3 isoforms expressed in photoreceptors

Abstract: The 14-3-3 family of proteins has undergone considerable expansion in higher eukaryotes with humans and mice expressing seven isoforms (β, ε, η, γ, θ, ζ, and σ) from seven distinct genes (YWHAB, YWAHE, YWHAH, YWHAG, YWHAQ, YWHAZ, and SFN). Growing evidence indicates that while highly conserved, these isoforms are not entirely functionally redundant as they exhibit unique tissue expression profiles, subcellular localization, and biochemical functions. A key limitation in our understanding of 14-3-3 biology lies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Specifically, 14-3-3s are small proteins that modulate cell growth and differentiation, regulation of apoptosis and cell cycle. Although the specific role of these proteins in retinal biology is not yet recognized, YWHAQ and YWHAE are the 14-3-3s proteins most highly expressed in the mouse retina and high levels of YWHAE are present in Rod photoreceptors [ 53 ]. Curiously, 14-3-3 proteins were found to interact with PDC, after its light-dependent phosphorylation, indicating that these may participate in facilitating the dark adaptation of the photoreceptor [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 14-3-3s are small proteins that modulate cell growth and differentiation, regulation of apoptosis and cell cycle. Although the specific role of these proteins in retinal biology is not yet recognized, YWHAQ and YWHAE are the 14-3-3s proteins most highly expressed in the mouse retina and high levels of YWHAE are present in Rod photoreceptors [ 53 ]. Curiously, 14-3-3 proteins were found to interact with PDC, after its light-dependent phosphorylation, indicating that these may participate in facilitating the dark adaptation of the photoreceptor [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our topological analysis showed that some genes targeted only by HXMMT had many other functions. For example, YWHAB may perform specific functions in rod photoreceptors [ 34 ]. RACK1 may promote the expression of VEGF in endothelial cells and subsequently facilitate angiogenesis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…YWHAE protein is widely expressed in eukaryote cells, and has been detected in wheat [19], giant trematodes in goat blood cells [20], liver ukes [21], and mosquitoes [22]. Moreover, in the physiological state of the human body, YWHAE was described as an important element in retinal photoreceptor rod cells [23]. Some researchers have found that YWHAE is also involved in the differentiation of adiposederived mesenchymal stem cells into osteoblasts, enhancing the body's osteogenic ability [24].…”
Section: Discussionmentioning
confidence: 99%